A review of railway sanding system research: Wheel/rail isolation, damage, and particle application. (July 2020) - Skipper, WA; Chalisey, A; Lewis, R
This paper reviews the academic and industrial research conducted into the practical aspects of using abrasive particles in the wheel/rail contact, such as: wheel/rail isolation, surface damage, and the application of the particles into the contact. Abrasive particles are applied to the wheel/rail contact to restore traction when low adhesion situations exist on the rail head; this process is referred to as "sanding" because sand particles are the preferred particle type in the railway industry. This aspect of sanding was covered in another sanding review. Currently, particles are applied either by firing dry particles into the wheel/rail contact via an air stream or by suspending them in a gel which can be applied using train-borne or trackside methods. The papers looked at in this review were scrutinised using a gap analysis method which grades each paper based on seven criteria, these criteria assessed: whether the papers had been peer reviewed, whether the conclusions matched the results, the range of testing scales used, and the presence of fundamental modelling work. When the findings of the research in this review were analysed, it was apparent that the negative effects of sanding (damage and isolation) have not been researched in much depth compared to its positive effects (adhesion restoration and leaf layer removal). In addition, the academic research that has been conducted has not been taken forward by industry, and industry research has not been studied in more depth by academia, suggesting a communication gap between the two branches of research; this was also the case for research into application methods.